Evaluation of Sustainable Development Indicators With Fuzzy TOPSIS Based on Subjective and Objective Weights - Nik Zahari, Nang Idayu; Abdullah, Mohd Lazim (IIUM Engineering Journal, 2012)
ABSTRACT: Sustainable development aims at improving and maintaining the well-being of people and the ecology. However, this paper focuses only on the ecological aspects. The selection of the proper ecological protection determinant plays a very important role in improving the environment of Malaysia. This paper will propose a method from Wang and Lee (2009), and Yong (2006) which applies a fuzzy TOPSIS method -- based on subjective and objective weights â€“ to make the required selection. Four alternatives will be tested which are: prevent pollution (A1), conservation (A2), well-manage (A3), and public awareness (A4). Along with these, four criteria need to be considered: water quality factor (C1), land integrity factor (C2), air quality factor (C3), and biodiversity factor (C4). Finally, a numerical example of ecological protection determinant selection is used to illustrate the proposed method.Â  ABSTRAK: Pembangunan lestari bermatlamat memperbaiki dan mengekalkan kesejahteraan rakyat serta ekologi. Walau bagaimanapun, kertas kajian ini hanya memberi tumpuan kepada aspek-aspek ekologi. Pemilihan penentu perlindungan serta keselamatan bagi aspek ekologi memainkan peranan yang amat penting dalam meningkatkan kualiti alam sekitar di Malaysia. Kertas kajian ini telah menggunakan kaedah Wang dan Lee (2009) dan Yong (2006) yang mengaplikasikan kaedah TOPSIS kabur berdasarkan pemberat subjektif dan objektif. Terdapat empat alternatif yang akan diuji iaitu: pencegahan pencemaran (A1), pemuliharaan (A2), pengurusan yang baik (A3), kesedaran orang awam (A4). Selain itu, terdapat empat kriteria yang perlu dipertimbangkan: faktor kualiti air (C1), faktor kualiti tanah (C2), faktor kualiti udara (C3), faktor kepelbagaian biologi (C4). Kesimpulannya, contoh pengiraan untuk memperoleh penentu pemilihan perlindungan ekologi telah digunakan bagi menunjukkan kaedah yang dicadangkan. KEYWORDS: sustainable development; ecological factors; subjective and objective weight; fuzzy TOPSIS